Experimental measurement and modeling of ion exchange equilibrium and kinetics of cadmium(II) solutions over microporous stannosilicate AV-6 - Simão P. Cardoso (2016)
Microporous stannosilicate AV-6 was investigated for cadmium(II) removal from aqueous solutions in batch experiments. Ion exchange equilibrium of the Cd2+/K+/AV-6 system was modeled using the mass action law combined with activity coefficient models for the solution (ideal, Debye-Htickel and Pitzer equations) and for the solid (Wilson equation) with absolute average relative deviations (AARDs) between 6.56% and 6.75%. It was concluded that the system embodies strong intraparticle non-idealities, namely solid activity coefficients between 0.2602 and 0.7180 for Cd2+. The kinetics of cadmium(II) sorption was analyzed measuring removal curves and modeling the data with pseudo-first and pseudo-second order expressions, commonly adopted in the literature, and with Maxwell-Stefan (MS) and Nernst-Plank (NP) based models. The best results were achieved by MS and NP approaches, for which AARD was 3.74% and 3.71%, respectively. The kinetic performance of the ion exchange was also discussed taking into account structural aspects of the AV-6 material.